The regulation and function of the striated muscle activator of rho signaling (STARS) protein - Wallace, Marita A. (Frontiers Media S.A., 2012)
Healthy living throughout the lifespan requires continual growth and repair of cardiac, smooth, and skeletal muscle. To effectively maintain these processes muscle cells detect extracellular stress signals and efficiently transmit them to activate appropriate intracellular transcriptional programs. The striated muscle activator of Rho signaling (STARS) protein, also known as Myocyte Stress-1 (MS1) protein and Actin-binding Rho-activating protein (ABRA) is highly enriched in cardiac, skeletal, and smooth muscle. STARS binds actin, co-localizes to the sarcomere and is able to stabilize the actin cytoskeleton. By regulating actin polymerization, STARS also controls an intracellular signaling cascade that stimulates the serum response factor (SRF) transcriptional pathway; a pathway controlling genes involved in muscle cell proliferation, differentiation, and growth. Understanding the activation, transcriptional control and biological roles of STARS in cardiac, smooth, and skeletal muscle, will improve our understanding of physiological and pathophysiological muscle development and function.